SEASONALITY IN LITTERFALL PRODUCTION IN A NATIVE FOREST IN THE CENTRAL REGION OF RS, BRAZIL - Vogel, Hamilton Luiz Munari; Lagemann, Monique Pimentel; Schumacher, Mauro Valdir (Floresta, 2020)
Studies on litter deposition are considered an important indicator of environmental quality of forest ecosystems. It is the main route of entry of organic matter and nutrients to forests. The objective of this study was to quantify the annual litterfall and seasonality in a fragment of native forest located in São Sepé in the Central Depression of Rio Grande do Sul. The experiment was conducted in a fragment of a Seasonal Semideciduous Forest. Inside this forest, in a place with homogeneous conditions, five plots of 20 m x 15 m length were systematically allocated 30 meters away from each other, where five litterfall traps were distributed in each plot (0,1963 m2 each trap), totaling 25 traps. The collection of all plant material deposited by the trees in the collectors was performed monthly in a four-year period. In the laboratory, the samples were separated into leaves, small twigs (diameter < 0.5 cm) and miscellaneous, and after they were oven dried and weighed on a precision balance. Higher litterfall was observed in the spring, with the highest return peaks mainly in October, indicating a seasonal deposition behavior. The mean litterfall was 6.56 Mg ha-1 year-1; of this total, the leaves were responsible for 67.61%, followed by the miscellaneous with 19.04% and the small twigs with 13.29%. Only a high significant correlation was obtained between the miscellaneous fraction and the temperature.